1998
DOI: 10.1074/jbc.273.40.26157
|View full text |Cite
|
Sign up to set email alerts
|

A High Fat Diet Impairs Stimulation of Glucose Transport in Muscle

Abstract: A high fat diet causes resistance of skeletal muscle glucose transport to insulin and contractions. We tested the hypothesis that fat feeding causes a change in plasma membrane composition that interferes with functioning of glucose transporters and/or insulin receptors. Epitrochlearis muscles of rats fed a high (50% of calories) fat diet for 8 weeks showed ϳ50% decreases in insulin-and contraction-stimulated 3-O-methylglucose transport. Similar decreases in stimulated glucose transport activity occurred in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
133
7
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 56 publications
21
133
7
1
Order By: Relevance
“…Numerous reports have focused on the role of high fat diets on insulin action in skeletal muscle [21,22,23,24,25]. Consistently, it has been reported that high fat diet increases the proportion of saturated fatty acids in the skeletal muscle membranes.…”
mentioning
confidence: 86%
“…Numerous reports have focused on the role of high fat diets on insulin action in skeletal muscle [21,22,23,24,25]. Consistently, it has been reported that high fat diet increases the proportion of saturated fatty acids in the skeletal muscle membranes.…”
mentioning
confidence: 86%
“…Glucose transport activity was measured as described (18). Intact soleus muscles, dissected from 8-week-old males, were preincubated for 15 min at 35°C in 2 ml of Krebs-Henseleit bicarbonate buffer, under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The lard/corn oil diet and other high-fat diets induce insulin resistance of muscle glucose transport in rats within a few weeks and, depending on type of fat and genetic background, diabetes in rats (25)(26)(27)(28). The flax seed/olive oil diet also results in decreases in insulin responsiveness of glucose transport in the slow-twitch red soleus muscle [2-deoxyglucose (2DG) transport: chow, 1.6 Ϯ 0.2 (basal) and 5.9 Ϯ 0.6 (insulin) mol⅐ml Ϫ1 ⅐30 min Ϫ1 versus high fat, 1.4 Ϯ 0.1 (basal) and 3.4 Ϯ 0.3 (insulin) mol⅐ml Ϫ1 ⅐30 min Ϫ1 , P Ͻ 0.05] and the fast-twitch white epitrochlearis muscle [2DG transport: chow, 0.52 Ϯ 0.07 (basal) and 2.5 Ϯ 0.2 (insulin) mol⅐ml Ϫ1 ⅐30 min Ϫ1 versus high fat, 0.53 Ϯ 0.05 (basal) and 1.8 Ϯ 0.14 (insulin) mol⅐ml Ϫ1 ⅐30 min, P Ͻ 0.05].…”
Section: The Flax Seed/olive Oil Diet Induces Insulin Resistance Of Mmentioning
confidence: 99%